Use of speech generating devices can improve perception of qualifications for skilled, verbal, and interactive jobs. - Stern, Steven E.; Chobany, Chelsea M.; Beam, Alexander A.; Hoover, Brittany N.; Hull, Thomas T.; Linsenbigler, Melissa; Makdad-Light, Courtney; Rubright, Courtney N. (Work, 2017)
BACKGROUND: We have previously demonstrated that when speech generating devices (SGD) are used as assistive technologies, they are preferred over the users' natural voices. OBJECTIVE: We sought to examine whether using SGDs would affect listener's perceptions of hirability of people with complex communication needs. METHODS: In a series of three experiments, participants rated videotaped actors, one using SGD and the other using their natural, mildly dysarthric voice, on (a) a measurement of perceptions of speaker credibility, strength, and informedness and (b) measurements of hirability for jobs coded in terms of skill, verbal ability, and interactivity. Experiment 1 examined hirability for jobs varying in terms of skill and verbal ability. Experiment 2 was a replication that examined hirability for jobs varying in terms of interactivity. Experiment 3 examined jobs in terms of skill and specific mode of interaction (face-to-face, telephone, computer-mediated). RESULTS AND CONCLUSIONS: Actors were rated more favorably when using SGD than their own voices. Actors using SGD were also rated more favorably for highly skilled and highly verbal jobs. This preference for SGDs over mildly dysarthric voice was also found for jobs entailing computer-mediated-communication, particularly skillful jobs.